2015
DOI: 10.1093/eurheartj/ehv111
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation and survival in a large representative community cohort of Dutch patients

Abstract: In a large and representative community cohort of Dutch patients with an ACS and/or intervention, CR was associated with a substantial survival benefit up to 4 years. This survival benefit was present regardless of age, type of diagnosis, and type of intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 31 publications
4
97
1
4
Order By: Relevance
“…An example of how routinely collected, real-world data can be used to assess the causal effects of treatment is provided by De Vries et al [15]. They investigated the effect of cardiac rehabilitation on survival using a large Dutch insurance claims database (n=35,919).…”
Section: Why Big Data Should Replace Traditional Medical Research Metmentioning
confidence: 99%
“…An example of how routinely collected, real-world data can be used to assess the causal effects of treatment is provided by De Vries et al [15]. They investigated the effect of cardiac rehabilitation on survival using a large Dutch insurance claims database (n=35,919).…”
Section: Why Big Data Should Replace Traditional Medical Research Metmentioning
confidence: 99%
“…Diese Fakten berücksichtigend ist somit jeder Arzt/jede Ärztin, der/die mit der Behandlung von Post-Myokardinfarkt-Patienten/innen betraut ist, gefordert, möglichst effektiv und langfristig Risiko-senkend zu agieren. Mehrere Studien und Metaanalysen der letzten Jahre haben rehabilitativen Maßnahmen einen Mortalitäts-Benefit bescheinigt [12,13] …”
Section: Langfristig Erhöhtes Risiko Nach Einem Akuten Koronarsyndromunclassified
“…28 Regarding specifically the trials on post-CABG-only article, 3 observational and nonrandomized articles are found (Table 2). Kutner and coworkers, 23 in a study with 6125 patients undergoing dialysis, found a 35% all-cause mortality and 36% cardiac death risk reduction after CR, although only 10% of the population participated in the program.…”
Section: How Strong Is the Scientific Evidence?mentioning
confidence: 99%